An Empirical Research on Fragile Eight Countries - Mete, Mustafa; Destek, Mehmet Akif (International Journal of Economics and Financial Issues, 2016)
This study investigates the possible reasons of the financial fragility of 10 countries with examining the stability properties of current account balance, budget balance and unemployment rate. For this purpose, the stability process of current account balance of 10 countries is examined for the period from 2005 to 2014; the unemployment of 10 countries is investigated for the period from 2004 to 2013; the budget balance of 8 countries is searched for the period of 2004-2012. The stability properties are examined using with panel unit root test and it is concluded that the current account of Chile and Indonesia is found stationary. In case of unemployment, stationary process is confirmed in South Africa, India, Poland and Indonesia. Finally, the stationary of budget balance is only supported in Brazil. Keywords: Fragile eight, Current Balance, Budget Balance, Unemployment JEL Classifications: F14, F37, G32